Hierarchical Hollow Bimetal Oxide Microspheres Synthesized through a Recrystallization Mechanism for High‐Performance Lithium‐Ion Batteries. Issue 16 (18th August 2020) - Li, Fanggang; Zheng, Maojun; You, Yuxiu; Jiang, Dongkai; Yuan, Hao; Zhai, Zhihao; Zhang, Wenlan; Ma, Li; Shen, Wenzhong
Abstract: Bimetal oxide with its intricate nanostructure holds great potential for high‐performance electrode materials in lithium‐ion batteries (LIBs). Herein, a facile strategy for the fabrication of hierarchical hollow Co3 O4 /ZnCo2 O4 microspheres is developed, involving a simple solvothermal synthesis and subsequent thermal annealing in air. An aggregation‐dissolution‐in situ recrystallization structure evolution and growth mechanism is proposed. Benefiting from the unique hierarchical hollow structure with rational porosity, synergistic effect of bimetal components, and better electrical conductivity, the as‐synthesized Co3 O4 /ZnCo2 O4 hierarchical hollow microstructure shows outstanding lithium storage properties. As a result, a superior rate capability (842 mA h g −1 at a current density of 4 A g −1 ) and an excellent cycle life (754 mA h g −1 after 800 cycles at a current density of 2 A g −1 ) are obtained. The presented strategy could be applicable to the synthesis of mixed metal oxide hierarchical hollow structures with rational porosity for high‐performance LIBs. Abstract : Has potential : A strategy involving an aggregation‐dissolution‐in situ recrystallization method followed by a thermal decomposition process is developed for the preparation of various hierarchical hollow microspheres composed of bimetal oxide nanoparticles without surfactant assistance. When investigated as anode materials for lithium‐ion batteries, the as‐synthesized hierarchical hollow microstructure exhibits superior rate capability and excellent cycle life.